Evaluation of Octyltetramethyldisiloxane‐Containing Ethylene Copolymers as Composite Lubricant for High‐Density Polyethylene. Issue 12 (28th September 2016) - Jin, Zhen; Fan, Hong; Li, Bo‐Geng; Zhu, Shiping
Abstract : A new type of siloxane‐containing ethylene copolymers, E‐co‐OO7, are evaluated as composite lubricant for high‐density polyethylene. The influences of the silicone content in the copolymer and the added copolymer amount in the blend on the bulk and surface properties of the blends are studied. E‐co‐OO7 shows overall superior performance in comparison with conventional lubricants (silicone masterbatch and PEwax). Abstract : A series of octyltetramethyldisiloxane‐containing ethylene copolymers, poly(ethylene‐co‐OO7) (abbreviated as E‐co‐OO7), are prepared from vanadium catalyzed copolymerization of ethylene with 1‐oct(7‐en)yl‐3‐octyl‐1, 1, 3, 3‐tetramethyldisiloxane (or OO7) macromonomer. The copolymers containing different silicone contents are employed as composite lubricants for high‐density polyethylene (HDPE). The influences of the silicone content in the copolymer and that of the added copolymer amount in the blend on the bulk and surface properties of the blends are systematically investigated. The results show that E‐co‐OO7 exhibits superior overall performance in comparison with conventional lubricants silicone masterbatch and polyethylene wax. Compared to HDPE control, 10 wt% E‐co‐OO7 addition increases the melt flow rates by 49%, increases the elongation at break from 740 to 860%, increases the water‐contact angle from 90° up to 108°, lowers the coefficient of friction from 0.072 to 0.049, lowers the specific wear rate from 11 × 10 −3 to 5.6 × 10 −3 mm 3 Nm −1 . The impact strength and high temperature thermal stability are also slightly improved. The measured Si/C atomic ratios demonstrate the sufficient silicone enrichment on surface of the blends. E‐co‐OO7 with 23.5 SiOSi per 1000 C gives the best internal lubrication, and E‐co‐OO7 with 29.7 SiOSi per 1000 C gives the best external lubrication.